Increasing Students’ Motivation to Write through Free Writing at the Second Semester Students of Accounting Study Program - Jayanti, Ade Dwi (LPPM Politeknik Raflesia, 2023)
The objective of the research: 1) To increase students’ writing skill through free writing 2) To increase students’ motivation to write through free writing. This research was implemented at the second semester students 2022/2023 of accounting study program in Politeknik Raflesia Rejang Lebong. Experimental research was used as a method in this research. The researcher took two classes, they are experimental class and control class. The data was gathered through test which are the pretest, the posttest and questionnaire. This research applied a quasi-experimental design in involved 35 students of two group. The experimental group was taught by using free writing, whereas the control group was taught conventional teaching, the data was obtained by using a pretest and a posttest. The pretest was given to both group before the treatment and posttest was given after treatment. The data were calculated by using computer program and manual. This reseacrh formulated two hypotheses, the null hypotheses were not effective and alternative hypotheses was effective in increasing students’ motivation to write by using free writing technique. After data tested and found to be homogneous and normal. The result of the research shows that t-test value is greater than t-table value (6.9 > 1.694) at level of significance (p) = 0.05 with degree of freedom (df) = 31. It means that there is a significant difference of writing skill between two classes and it indicates that null hypotheses (H0) is rejected and alternative hypotheses (H1) is accepted. Therefore, based on the findings and discussion of this research, it can be concluded that the free writing effectively in increasing students’ motivation to write at accounting study program in Politeknik Raflesia.